Globalization and conflict in educational system: Opportunities and challenges in lifelong learning in Nigeria and Malaysia - Halliru, Tijjani (2010)
Since the emergence of globalisation as the new world order in the 21st century, revolution in social, economic, political and technological development became not only necessary but inevitable. However, education remain the driving force through which globalization can thrive. Against this backdrop, developing countries such as Nigeria and Malaysia were left with no option than to introduce lifelong learning as an appendage to the full time school system to facilitate reduction in illiteracy level and mitigate effects of globalization. In Malaysia, so much human and material resources have been channelled (especially with the establishment Open Distance Learning (ODL) to fast track the program keeps moving. In Nigeria unlike Malaysia, the establishment of lifelong centres popularly called Distance Learning Centres (DLS) and the subsequent introduction of National Open University of Nigeria (NOUN) was besieged by population growth, high demand for education in the mist of underfunding, poverty, instability and conflict. To overcome this malaise, developing countries as nation states must re-define its policies on education, increase budgetary expenditures, reduce poverty and institutionalize democracy and good governance in order to suit and be suitable to the globalized world. To arrive at the above conclusion, the study relied on content analysis of secondary sourced materials mainly from journals and text books.